Notifiche
Cancella tutti

algebra help

  

0

algebra espressione monomi 

img 20230124 225140 478872468955278247

 

Autore
2 Risposte
5

a^5b^2c^4(-1+2/3+5/6)/(-5/4a^3b^2c^3)=

=a^2c(-6+4+5)/6*(-4/5)= 1/2*(-4/5)a^2c =-2/5*a^2c




4
image

----------------------------------------------------------------

$\frac{-a^5b^2c^4+\frac{2}{3}a^5b^2c^4+\frac{5}{6}a^5b^2c^4}{-\frac{5}{4}a^3b^2c^3}$ =

= $\frac{\big(\frac{-6+4+5}{6}\big)a^5b^2c^4}{-\frac{5}{4}a^3b^2c^3}$ =

= $\frac{\frac{3}{6}a^5b^2c^4}{-\frac{5}{4}a^3b^2c^3}$ =

= $\frac{\frac{1}{2}a^5b^2c^4}{-\frac{5}{4}a^3b^2c^3}$ =

= $ \frac{1}{2}\big(-\frac{4}{5}\big)a^{5-3}b^{2-2}c^{4-3}$ =

= $-\frac{4}{10}a^2b^0c^1$ =

= $ -\frac{2}{5}a^2c$

Risposta



About SosMatematica

Seguici su:

Scarica la nostra App Ufficiale

SOS Matematica


SCARICA